EVALUASI PERKEMBANGAN TERNAK KAMBING PADA KELOMPOK USAHA TANI, BANTUAN PEMERINTAH DI KABUPATEN POSO - Kasim, Kaharuddin (FAPETKAN UNTAD, 2011)
A study was undertaken on eight farmer groups at Poso District. The aim of the study was to evaluate the pattern growth of goat population given as a government support. The study was conducted for 2 months from July to September 2010. This study was consisted of a survey and direct interview with the goat farmers. Investigated variables were: a) livestock composition at initial population (adult male and female); and at the present time (adult male and female, young goat (>6 months old) and kits, b) rearing management for goat development such as breeding method, mating age, weaning age and birth intervalÂ to each of the involved farmer groups. In addition, other considered aspects were housing type, feeds and feeding interval and diseases. Results of the study indicated that: 1) technical coefficient of reproduction such as, weaning age, mating age, birth interval and breeding method did not follow the existing recommended technique on livestock reproduction, therefore the expected growth pattern of the goat population was not achieved; 2) housing system was good enough, only two groups (25%) of the 8 farmer groups has still used soil ground floor and the remaining 75% used stable stage; 3) all the farmer groups experienced with various (4-7) feedstuffs and different feeding intervals and techniques (1.5 â€“ 2 times /day); and 4) high diseases invasion due possibly to feed availability, both qualitatively and quantitavely. Key words : Coefficient of reproduction technigue, operational management, and productivity.